Kindness Media Rapidly Inspires Viewers and Increases Happiness, Calm, Gratitude, and Generosity in a Healthcare Setting - Fryburg, David A.; Ureles, Steven D.; Myrick, Jessica G.; Carpentier, Francesca Dillman; Oliver, Mary Beth (Frontiers in Psychology, 2021)
Background and objectives: Stress is a ubiquitous aspect of modern life that affects both mental and physical health. Clinical care settings can be particularly stressful for both patients and providers. Kindness and compassion are buffers for the negative effects of stress, likely through strengthening positive interpersonal connection. In previous laboratory-based studies, simply watching kindness media uplifts (elevates) viewers, increases altruism, and promotes connection to others. The objective of the present study is to examine whether kindness media can affect viewers in a real world, pediatric health care setting. Methods: Parents and staff in a pediatric dental clinic were studied. Study days were randomized for viewers to watch either original kindness media or the standard televised children’s programming that the clinic shows. Participants scored self-rated pre-media emotions in a survey, watched either media type for 8 minutes, and then completed the survey. All participants were informed that they would receive a gift card for their participation. After completion of the survey, participants were asked if they wanted to keep the card or donate it to a family in need. Results: 50 participants completed the study; 28 were parents and 22 were staff. Participants who watched kindness media had significant increases in feeling happy, calmer, more grateful, and less irritated (p<0.05), with trends observed in feeling more optimistic and less anxious. Kindness media caused marked increases in viewers’ reports of feeling inspired, moved, or touched (p<0.001). No change was observed in self-reported compassion, although baseline levels were self-rated as very high. People who watched kindness media were also more generous, with 85% donating their honoraria compared to 54% of Standard viewers (p=0.03). Conclusions: Kindness media can increase positive emotions and promote generosity in a health care setting.